Innovative development and human capital as determinants of knowledge economy - Olha Podra; Nataliia Litvin; Zinaïda Bohdanivna Žyvko; Marta Kopytko; Liliia Kukharska (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The development of a knowledge economy is a key priority for innovative progress and for ensuring the country's competitiveness through the efficient use of intellectual resources and human capital. Our paper is focused on a necessity to find out the influence of human capital in providing innovative development and the formation of knowledge economy, to develop measures for its formation, accumulation, preservation, reproduction in order to increase national competitiveness at the world market. The foundation of the knowledge economy is productive knowledge and quality education that contribute to the intellectual capital embodiment into productive activities. A detailed analysis of the current state and problems of the education and science spheres has been carried out, international ratings have been analyzed and the place of Ukraine in them is determined in the article. An estimation of financial losses of the economy in connection with the outflow of students to study abroad is hold in the article. By using the trend modeling method we propose to estimate the effect of the predicted values of the components of innovation activity on the Global Innovation Index. Results show that Ukraine position in the Global Innovation Index rating will strengthen, which can testify, about the redistribution of financing of the innovation sphere in favor of private institutions and investors. The transition to a knowledge economy involves an understanding of the decisive influence of science, the latest technologies, innovations in the global economy, and enables the resource-oriented countries to leave this status and become a countries of high-tech and high skilled development, based on the transformation of knowledge into a source of value and the driving force of economic progress.
Keywords: G32; 650; knowledge economy; innovative development; human capital; intellectual capital